P-138 St Oswald's Hospice Ambulatory Care Service progress after one year. (19th November 2022) - Lever, Owen; Saunderson, Jen; Brown, Jo; Clark, Kath
Abstract : Background: For patients with chronic, life-limiting haematological conditions such as Myelodysplastic syndrome (MDS), regular transfusion for symptom relief requires frequent hospital attendances. Literature demonstrates MDS is associated with significant impairment, poor prognosis and critical palliative care needs (Nickolich, El-Jawahri & LeBlanc, 2016. Curr Hematol Malig Rep. 11:434). St. Oswald's Hospice Day Services has developed an Ambulatory Care service for patients requiring transfusions and other infusions, working with specialties to offer services to patients who would benefit from earlier palliative care support. Method: We have collected data on attendance/treatments to demonstrate the scope of the service and reviews by members of the hospice MDT, including in-patient admission, demonstrating needs met by this service which may not have been available in a non-hospice setting. Results: From March 2021 to May 2022 there have been 32 patients with 232 individual attendances and 456 treatments administered: 426 units blood. 9 pools platelets. 8 Iron infusions. 2 Bisphosphonate infusions. 10 IV antibiotic. 1 B12 Injection. MDT members seen: 32/32- assessment with a senior Palliative Medicine Doctor. 32/32- medical review every attendance. 32/32- Hospice Nurse review every attendance. 16/32- Complementary Therapy. 7/32- Social Worker. 6/32- Physiotherapist. 5/32- OT. 2/32- Referred for Music Therapy. 2/32- Lymphoedema Practitioner. 1/32- Referred to Psychology. 1/32- Spiritual Care Team. Inpatient Admissions: 7 hospice admissions relating to the Ambulatory Care Service: 2 direct admissions from Ambulatory Care attendance 5 indirect admissions from home/hospital for patients known to the ambulatory care service. Conclusion: Patients have accessed services from the hospice MDT that may not have been available to them had they not been attending the Ambulatory Care service. Increasing the number of referrals to the service will continue to widen access to patients not typically referred until later in their disease process, promoting improved quality of life and advance care planning.